Comprehensive development, uncertainty and sensitivity analysis of a model for the hydrolysis of rapeseed oil. (2nd February 2020) - Forero-Hernandez, Hector; Jones, Mark Nicholas; Sarup, Bent; Jensen, Anker Degn; Abildskov, Jens; Sin, Gürkan
Abstract: A model describing the batch hydrolysis of rapeseed oil including kinetics and mass transfer at subcritical conditions is presented in this paper. The primary purpose of this model is to interpret experimental data collected from typical batch tests and to estimate model parameters. The developed model was further investigated using Monte Carlo simulations to statistically quantify the variability in the model outputs due to uncertainties in the parameter estimates. To understand which parameters in the model are responsible for the output uncertainty, a sensitivity analysis method was used (polynomial chaos expansions-based Sobol sensitivity indices). The results from the sensitivity analysis helped to identify what parameters in the model are influential, giving insight into the robustness and predictive capabilities of the model which form the basis for any model-based decision making for detailed process characterization, design, optimization and operation of the hydrolysis of rapeseed oil.